Personality effect on decision-making among normal university students and comparing gambling task performances of normal university students with a group of normal adults - YILDIRIM, MELİS SERAY ÖZDEN (My University, 2012)
In daily life, individuals with decision making deficit, don’t learn from negative feedbacks in risky situations and for this reason they fail in social life. The Iowa Gambling Task (IGT) is a neuropsychological test that assesses decision making in daily life through components reward, punishment and ambiguity. In this study, IGT was given to a university student population consisted of 107 participants between ages of 20-25 and 90 participants between ages of 25-60+. The most important finding of the study is performance differences between age groups on their IGT scores and the personality effect on IGT performances of post adolescents.
Keywords: Personality; decision-making; gambling task performance